The Effect of Healthy Lifestyle Educational Program on Rural Elderly's Quality of Life in Dashti District of Boushehr Province - Akram Farhadi; Mahshid Foroughan; Farahnaz Mohammadi; Mohsen Sahranavard (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Life expectancy has been increased over the world and the number of older people is increasing, concomitantly. In recent years, not only the quantity of life of elderly (the years to stay alive), but the quality of it (how to live it) are considered important. This includes the elderly living in rural areas, as well as, the elderly living in urban areas.This study intends to survey effect of healthy lifestyle educational program on quality of life of rural elderly in Dshti District of Boushehr Province. Methods & Materials: This study is semi experimental design, pretest-posttest with control group. Society of this study was all rural elderly in Dshti District of Boushehr Province in February 2010,with Using of multistage cluster sampling, 79 rural elderly who had inclusion criteria (including not having severe and disabling chronic diseases) were selected as samples. to collect data was used from a questionnaire measuring knowledge and healthy lifestyle & SF-36 questionnaire Data gathering was done with face to face interview method and the statistical software SPSS17 were used for data analysis. collected data were analyzed with using statistical methods repeated ANOVA, analysis of covariance, post hoc test Bonferroni and chi squere. Results: The results showed that knowledge of healthy lifestyles, as well as quality of life of rural elderly in Dashti District of Boushehr Province were low & healthy lifestyle educational program promote knowledge of healthy lifestyles and improve quality of life in elderlyof tested group (P<0.05), While the quality of life and knowledge of healthy lifestyle elderly of control group will decrease, but this reduction was not statistically significant (P>0.05). Conclusion: So that healthy lifestyle education program improves quality of life of rural elderly in Dashti District of Boushehr Province.